The relationship between joint damage and functional disability in rheumatoid arthritis: a systematic review. Issue 6 (29th November 2011) - Bombardier, Claire; Barbieri, Marco; Parthan, Anju; Zack, Debra J; Walker, Valery; Macarios, David; Smolen, Josef S
Abstract : Objective: To summarise the relationship between joint damage and functional disability in rheumatoid arthritis (RA) patients. Methods: A systematic review of the literature from 1990 to 2008 was conducted using MEDLINE and EMBASE databases. The search strategy focused on RA, joint damage and disability. Only longitudinal studies or randomised clinical trials with 1 year or more of follow-up containing data correlating joint damage and disability were included. The comparisons were categorised in four ways: baseline damage versus disability at end of follow-up (correlation A); damage versus disability measured cross-sectionally at each of several time points (correlation B); changes in damage versus final disability (correlation C) and changes in damage versus changes in disability (correlation D). Results: From a total of 1902 abstracts, 42 studies met the inclusion/exclusion criteria. More than 50% of the studies that measured baseline damage to later disability (A) reported a statistically significant association. Correlation was significant when measured at multiple time points over time (B; 16/19 studies). Statistically significant associations between changes in damage and either disability at end of follow-up or changes in disability were also found (C and D; 11/13 studies). Conclusions: While many of the studies did not include multivariate analysis with confounder adjustment, the published evidence indicates a link between joint damage and functional disability and that an increase in joint damage is associated with an increase in disability over time. Treatments to limit progressive joint damage may lead to better joint function and improved patient outcome with less disability.